Documentation of the Bantu language Mpiemo of the Central African Republic (A86c)_3 - Thornell, Christina (University of Gothenburg, 2014)
The overall aim of the study has been to document and preserve the minority language Mpiemo as well as to analyse it from a linguistic perspective. The language is spoken in some regions of the Central African Republic and Cameroon. The language is classified as A86c according to the Guthrie system and has approximately 29,000 speakers. When the project started there was a translation of the four gospels with a French-based orthography, but no other texts. The documentation has spanned several projects from 1998 onwards and has resulted in, amongst other things, a number of articles on Mpiemo phonetics, phonology, morphology as well as the publication of recorded speech together with transcripts and annotations and texts about the local wild plant life.

Purpose:

The purpose of the project has been to document and linguistically analyse the Central African language Mpiemo by means of varying subprojects.

The dataset contains soud recordings of several texts. Matthew chapter 8 is read by a Mpiemo speaker (Mathurin Mpatoumbo). There are also PDF files of the text which follow the translation made by Gilbert Ankouma, Joseph Apang and Lydia Lundström (1978).
The fable Mpi na kubɔ (The dog and the hen) was written down by a native speaker of Mpiemo (Jean-Charles Ankouma) and was then edited together with him and another person (Mathurin Mpatoumbo). The fable was then recorded. Both a sound recording and a transcript with annotation are available.
There are also some proverbs collected by Mathurin Mpatoumbo. They are only available as sound recordings. The proverbs are translated into the Sango language but not into French. The reason for this is that they exist in the Sango culture but not in the French.

Studiens övergripande syfte har varit att dokumentera och bevara minoritetsspråket mpiemo samt att analysera det ur ett lingvistiskt perspektiv. Språket talas i delar av Centralafrikanska republiken och Kamerun. Språket klassificeras som A86c enligt Guthrie-systemet och har runt 29 000 talare. Då projektet började fanns en översättning av de fyra evangelierna med fransk-baserad stavning men inga andra texter. Dokumentationen har sträckt sig över flera projekt från 1998 och framåt och har bland annat resulterat i en rad artiklar om mpiemos fonetik, fonologi, morfologi och även publicering av inspelat tal med transkriptioner och annoteringar och texter om vilda växter i området.

Syfte:

Syftet med projektet har varit att genom olika delprojekt dokumentera det centralafrikanska bantuspråket mpiemo och göra lingvistiska analyser på materialet.

Datasetet innehåller inspelningar av några olika texter. Matteus kapitel 8 läses av en mpiemotalare (Mathurin Mpatoumbo). Det medföljer också PDF-filer med texten enligt översättning av Gilbert Ankouma, Joseph Apang och Lydia Lundström (1978).
Fabeln Mpi na kubɔ (Hunden och hönan) har skrivits ned av en modermålstalande mpiemoperson (Jean-Charles Ankouma) och sedan vidare bearbetats tillsammans med honom och ytterligare en person (Mathurin Mpatoumbo). Fabeln har sedan spelats in. Det finns tillgång till ljudinspelning och transkription med annoteringar.
Finns även några ordspråk samlade av Mathurin Mpatoumbo. Dessa finns endast som ljudfiler. Ordspråken är översatta till sangospråket men inte på franska. Anledningen är att de finns i sangokulturen men inte i den franska.
Dokumentation av det centralafrikanska bantuspråket mpiemo (A86c)_3
Keywords: minority languages; minoritetsspråk; folklore; folksagor; translation; översättning; linguistics; lingvistik; linguistic analysis; lingvistisk analys; speech; tal (muntligt); literature; litteratur; Mpiemo; mpiemo; Bantu languages; bantuspråk; A86c; A86c; Bibel text; bibeltext; fable; fabel; proverb; ordspråk; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk